A NEURAL NETWORK MODEL FOR AUTOMATED LOGISTICS PROVIDER SELECTION - Mirzanova Nozima Maratovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In the article, using artificial intelligence technologies in the digital economy, the problems of organization of logistics flows were identified and scientific proposals aimed at solving them were developed